Prediction of the Total Biomass and Yield of Pearl Millet using Solar Radiation and Spectral Measurements - Niwas, Ram; Sastry, C V.S (Annals of Arid Zone, 2016)
Multiple linear regression models were developed for prediction. of pearl millet dxy biomass and yield under agroclimatic conditions of Delhi. A stepwise regression analysis was carried out to select the best agrometeorological (absorbed photosynthetically active radiation, evapotranspiration and thermal interaction rate) and spectral indices (infra redlred ratio and no;malised difference) which explained maximum variation in dxy biomass and. yield. The R- values obtained were 0.973 and 0.995 for dry biomass and yield models, respectively.